External Threats to the Cohesion of the EU: a Comparative Study of Elites’ Perceptions - Matonytė, Irmina; Morkevičius, Vaidas (Sociologija. Mintis ir veiksmas, 2009)
One of the important constituents of common identity is a perception of the same external others as threats. Therefore, European identity construction should be grounded in similar perceptions of threats and European elites – a group having the most important influence on the construction of the common European identity – should share similar perceptions of these threats. In this study elites’ perception of 3 potential external threats to the cohesion of the EU have been investigated: enlargement of the EU to include Turkey, close relationships between some EU countries and the United States, and interference of Russia in European affairs. Analysis of the Belgian, German, Polish and Lithuanian elite survey data shows that the most abstract level there is no common European identity constructed across the selected European states. It appeared that distinct European identities emerge along the new-old EU member-states divide. At the same time, individual level factors such as elite left-right self-identification, different visions of the role and future of the EU as well as type of the preferred national identity (achieved vs. ascribed) significantly shape perceptions of external threats and therefore constitute the grounds for the formation of distinct European identities.